Resilience, personal recovery, and quality of life for psychiatric in-patients prior to hospital discharge: demographic and clinical determinants - Owusu, Ernest; Mao, Wanying; Shalaby, Reham; Elgendy, Hossam Eldin; Agyapong, Belinda; Eboreime, Ejemai; Lawal, Mobolaji A.; Nkire, Nnamdi; Hilario, Carla T.; Wei, Yifeng; Silverstone, Peter; Chue, Pierre; et al. (Frontiers in Psychiatry, 2025)
IntroductionPatients with mental health challenges often see the transition from hospital to community as a test of resilience and a potential threat to recovery. Many question their ability to cope with everyday challenges. This paper examines how demographic and clinical factors predict resilience, personal recovery, and quality of life.MethodsData were collected from psychiatric inpatients before discharge using REDCap, an online survey platform. Resilience, recovery, and quality of life were assessed with the Brief Resilience Scale (BRS), Recovery Assessment Scale (RAS), and EQ-Visual Analogue Scale (EQ-VAS). ANCOVA was used to compare group relationships. Demographic and clinical variables such as age, gender, ethnicity, and mental health diagnosis were independent variables.ResultsMales had significantly higher resilience scores than females (Mdiff = 0.270, p<.001) and others (Mdiff = 0.470, p<.001). Self-identified Black individuals had higher quality of life scores than Caucasians (Mdiff = 8.79, p<.001) and Indigenous individuals (Mdiff = 14.50, p<.001). Participants with depression had significantly lower recovery scores compared to those with bipolar disorder (Mdiff = -10.25, p<.001), schizophrenia (Mdiff = -8.60, p<.001), and substance use disorder (Mdiff = -8.30, p<.005).ConclusionResults suggest that women, younger adults, Indigenous peoples, and individuals with depression struggle more with adapting to post-discharge life. Policymakers should implement programs that focus on supporting resilience in these vulnerable groups.